KLASIFIKASI EMOSI DALAM LAGU BRUTAL KARYA OLIVIA RODRIGO - Yulan Putri Ananti; Erik Candra Pertala; Siska Hestiana (Nusantara Hasana Journal, 2023)
Emotions can be owned by every human being. The emotions they have also vary, depending on the situation and conditions they are experiencing. Emotions can be expressed or suppressed by someone. However, some people can also express their emotions through a song. As it was done by Olivia Rodrigo. His song entitled Brutal is a song that describes the feelings she experienced when he was a teenager. Therefore, in this song there must be an emotion that we can find in the lyrics of the song. This study aims to determine the emotions contained in the Brutal song by using Minderop's theory of 7 classifications of emotions. This research is descriptive qualitative, because the research results are in the form of data not in the form of numbers. Due to qualitative research, the data collection that will be carried out is observing and noting. The author will listen to the lyrics of the Brutal song and analyze it using the existing theory. The data obtained will be recorded immediately.